Developing creative activity abilities of students in higher educational establishments - Dorofeev, Sergey Nikolaevich; Shichiyakh, Rustem Adamovich; Khasimova, Leisan Nafisovna (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
The article discusses methods for solving geometric problems with the active use of methods such as analysis and synthesis, analogy and generalization, based on theoretical thinking on the principle of ascent from simple to complex in order to develop students' ability to creative activity. The authors have developed systems of problems, focused on the formation of their ability to "make" independent discoveries both in the process of solving a problem and at the stage of researching the result of the solution. The developed system of problems is aimed at finding a way to solve a more complex problem, after a similar method has been used in relation to another simpler or particular problem. The participants in the experiment are future masters of pedagogical education (profile "Mathematical Education") at Togliatti State University. The article shows that the most effective methods of preparing future masters of mathematics education for creative professional activity can be such methods of scientific knowledge as analogy and generalization. It was revealed that in the process of learning to solve geometric problems included in the developed system, students demonstrate higher indicators of the level of formation of creative activity, as a result of the development of the ability of the future master of pedagogical education (profile "Mathematical Education") to analogy and its application in specific situations, his ability to use the established properties, skills and abilities formed, techniques and methods of action in relation to another object in new conditions and for new purposes, the use of mathematical concepts and theorems in more and more diverse specific problems.